Revealing nanoscale strain mechanisms in ion-irradiated multilayers. (1st May 2022) - Daghbouj, N.; Sen, H.S.; Callisti, M.; Vronka, M.; Karlik, M.; Duchoň, J.; Čech, J.; Havránek, V.; Polcar, T.
Abstract: Tailoring interfaces is a powerful way of reducing the accumulation of radiation defects. Understanding strain evolution induced by ion bombardment in nuclear materials with high interface density is crucial for next-generation reactors since induced defects are responsible for volumetric swelling and catastrophic failure. X-ray and selected-area diffraction patterns (SADPs) measurements reveal, after Cu implantation, that a relatively high out-of-plane strain is created in thin Zr/Nb6 multilayers, while thick Zr/Nb96 is barely distorted. The absence of layer deformation in Zr/Nb96 is explained by local TEM strain mapping showing the presence of two oppositely distorted regions (inner and interface-affected regions) within one layer producing only a small overall strain, whereas the whole individual layers of Zr/Nb6 are affected by the interface manifesting high strain. Using MD simulations, the types of defects responsible for layer distortion are identified. The opposite distortion within the layer is attributed to the inequality of the defect flux from the inner to interface-affected region due to the difference in migration energy barriers of the point defects. Moreover, the interface sink efficiency (defect annihilation) is determined for Zr/Nb as an illustration which provides a strategy for designing new derivate structures of multilayers with high radiation damage resistance. Graphical abstract: Image, graphical abstract